RTOS-BASED DIGITAL ELECTRICITY METER IMPLEMENTATION WITH THE USE OF ESP32 AND LORA SECURED COMMUNICATION - Naufal Thariq, Muhammad
In fulfilling the ideal conditions for electrification efforts in remote areas, there are inefficiencies regarding the implementation of the Rural Mini-grid Management (RUMI) Model using PV-based power plants since the current system does not require electricity customers to make periodic payments. In this thesis, the author will develop a digital electricity meter system that integrates a remote monitoring mechanism for customer energy consumption, a prepaid payment method that is directly connected to the meter, and a remote control mechanism for electric flow. During development, the author will determine the product specifications to be designed based on the problem analysis that has been performed beforehand. This is followed by designing and implementing the system under the product specifications. Finally, testing must be carried out to ensure system functionality and to ensure system performance according to predetermined specifications. In this solution, the author has developed a digital power meter that can be controlled remotely. This meter used a LoRa-based communication with the payload adjusted to the meter’s optimum distance from the communication gateway. The use of a Real-Time Operating System (RTOS) embedded on the ESP32 microcontroller allows the meter to do a lot of tasks in an instance. Control of electricity at the customer’s household can be controlled remotely based on a Finite State Machine (FSM) which is optimized with the solution to this problem. Also, energy consumption in households can be monitored by operators and customers to clarify and simplify customer payment schemes that are integrated directly with digital meters. The meter has been functioning properly based on functional tests that have been carried out during the testing phase of this thesis. However, the COVID-19 pandemic in 2020 has hampered the process of testing the meter’s performance. Therefore, further testing regarding the meter’s performance should be conducted by those who plan to continue this project.